(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The authors arrange a round table conversation to analyses and discuss the most significant topics in Indian management research. They worry about the inclination of Indian researchers to unquestionably replicate western research and publication practices. They advocate self-assured indigenous scholarship, which meets the growth and educational requirements of the country through the use of research frameworks and methodologies as well as separately evolving curricula, content and distribution methods, with the same rigor as the Western models, at the IIM Bangalore in December 2011. Initially, the critique of the so-called US study technique completely disregards the subject. Obviously, the models must have climate, but it is like the forest for trees being completely ignored. We only begin to appreciate a player after they have won a worldwide battle, irrespective of their number of competitions.